Neon Fluor et cie : exposition. - Benthall, Jonathan; Bouteas, Yanis; Brys-Schatan, Gita; Eizykman, Boris; Hissard, J.R.; Lhermitte, J.L.; Moles, Abraham A.; Reichardt, Jasia; Van Lier, Henri; Weckerle, Christian; ISELP (Institut Supérieur pour l'Etude du Langage Plastique), Bruxelles (Brussel : ISELP (Institut Supérieur pour l'Etude du Langage Plastique) Bruxelles, 1984)
Bouteas, Yannis ; Burgering, Toni ; Buscarlet, Alain ; Chryssa, Varda ; Copers, Leo ; Decelle, Philippe ; Flausch, Fernand ; Riverhead (New York) ; Gasparotto, Paolo ; Van Herck, Frank ; van der Horst, Jozef ; Kosuth, Joseph ; Kowalski, Piotr ; Lambert, Henri ; Laval, Antoine ; Matthys, Danny ; Merz, Mario ; Metallicavau ; Morellet, François ; Pompon, Rosalie ; Rensonnet, Pierre-Philippe ; Sarkis ; Sonnier, Keith ; Steinfort, Patrick ; Stevens, Bruno ; Vertessen, Liliane ; Villers, Bernard ; De Witte, Jean-François
biog., tent. per kunstenaar, Les événements Néon p. 12-14
Engels
Frans
Neon Fluor et cie, ISELP (Institut Supérieur pour l'Etude du Langage Plastique) Bruxelles, 15.09 - 12.10.1984
boek